2013
DOI: 10.1111/jcmm.12096
|View full text |Cite
|
Sign up to set email alerts
|

Identification of micro‐RNA networks in end‐stage heart failure because of dilated cardiomyopathy

Abstract: Micro-RNAs regulate gene expression by directly binding to the target mRNAs. The goal of the study was to examine the expression profiling of miRNAs in human failing hearts and identify the key miRNAs that regulate molecular signalling networks and thus contribute to this pathological process. The levels of miRNAs and expressed genes were analysed in myocardial biopsy samples from patients with end-stage heart failure (n = 14) and those from normal heart samples (n = 8). Four networks were built including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…However, there are few data on miRNA expression within the myocardium of patients with heart failure. That which is available comes from studies done on explanted hearts taken at the time of transplantation [17][18][19] and there appears to be no data derived from myocardial biopsy tissue taken from patients with less extreme disease or early onset heart failure. Therefore in this study we have explored the expression of selected myocyte and fibroblast-specific miRNAs known to be involved in the processes of hypertrophy, apoptosis and fibrosis in myocardial biopsy specimens taken from patients admitted with heart failure compared with a group of patients without heart failure undergoing routine cardiac surgery.…”
Section: Introductionmentioning
confidence: 95%
“…However, there are few data on miRNA expression within the myocardium of patients with heart failure. That which is available comes from studies done on explanted hearts taken at the time of transplantation [17][18][19] and there appears to be no data derived from myocardial biopsy tissue taken from patients with less extreme disease or early onset heart failure. Therefore in this study we have explored the expression of selected myocyte and fibroblast-specific miRNAs known to be involved in the processes of hypertrophy, apoptosis and fibrosis in myocardial biopsy specimens taken from patients admitted with heart failure compared with a group of patients without heart failure undergoing routine cardiac surgery.…”
Section: Introductionmentioning
confidence: 95%
“…In left ventricle tissue samples, cardiac hypertrophy induced by volume overload resulted in increased expression of miR-340 as shown by RT-PCR analysis ( Figure 1E), which was in accordance with previous human HF results. 11) We also detected the expression of CT-1, and its expression was elevated as expected ( Figure 1F). This in vivo study further confirmed the induction effect of CT-1 on miR-340.…”
Section: Volume Overloaded Cardiac Expression Of Mir-340 During the Dmentioning
confidence: 64%
“…In view of the effect of mechanical stretch on the induction of CT-1, 20) dysregulated hemodynamics may be the initiator of miR-340. In a previous study, upregulated miR-340 was seen in HF patients because of dilated cardiomyopathy, 11) so volume-overload may be the initiating factor participating in the activation of miR-340.…”
Section: )mentioning
confidence: 99%
“…A distinct miRNA profile was revealed in the failing hearts of DCM patients, and miR-340 was identified as a key miRNA in regulating the structure of cardiomyocytes (15). A low let-7i level was found in endomyo- Role of miRNA-451a in dilated cardiomyopathy APRIL 7, 2017 • VOLUME 292 • NUMBER 14 cardial biopsy tissues from DCM patients compared with those from control subjects and was correlated with high Toll-like receptor 4 protein level and associated with poor clinical outcomes (16).…”
Section: Discussionmentioning
confidence: 99%